Assessment and analysis of information quality: a multidimensional model and case studies. (23rd November 2011) - Berti-Équille, Laure; Comyn-Wattiau, Isabelle; Cosquer, Mireille; Kedad, Zoubida; Nugier, Sylvaine; Peralta, Verónika; Cherfi, Samira Si-Saïd; Thion-Goasdoué, Virginie
Information quality is a complex and multidimensional notion. In the context of information system engineering, it is also a transversal notion and to be fully understood, it needs to be evaluated jointly considering the quality of data, the quality of the underlying conceptual data model and the quality of the software system that manages these data. This paper presents a multidimensional model for exploring information in a multidimensional way, which aids in the navigation, filtering, and interpretation of quality measures, and thus in the identification of the most appropriate actions to improve information quality. Two application scenarios are presented to illustrate and validate the multidimensional approach: the first one concerns the quality of customer information at Electricité de France, a French electricity company, and the second concerns the quality of patient records at Institut Curie, a well-known medical institute in France. The instantiation of our multidimensional model in these contexts shows first illustrations of its applicability.